2022
DOI: 10.1101/2022.02.21.480960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insights into the ribosome function from the structures of non-arrested ribosome nascent chain complexes

Abstract: During protein synthesis, the growing polypeptide chain threads through the nascent peptide exit tunnel that spans the body of the large ribosomal subunit while simultaneously acting as a modulator of ribosomal activity by itself or by sensing various small molecules, such as metabolites or antibiotics appearing in the tunnel. While arrested ribosome nascent chain complexes (RNCCs) have been extensively studied structurally, little attention has been given to the RNCCs that represent the functionally active st… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The distance between the α-amine and reactive carbonyl for a properly positioned α-amino acid is 2.9 - 3.3 Å with the expected Bürgi-Dunitz angle of 90-110° (Figure 3A). 5,16,28 Comparison of the three cryo-EM models with aminobenzoic acid monomers in the A site revealed that, while the conserved base pair between C75 in A-site tRNA and G2553 in 23S rRNA is retained (Figure 2), the positioning of the aromatic ring in the A-site cleft formed by A2451 and C2452 shifts the position of the monomer within the PTC, especially the nucleophilic amine, relative to that of an l -α-amino acid (Supplementary Figure S12). In the case of the m ABZ monomer, the aromatic ring could be modeled in two distinct conformations that differ by a 180° rotation about the aryl-carbonyl bond (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distance between the α-amine and reactive carbonyl for a properly positioned α-amino acid is 2.9 - 3.3 Å with the expected Bürgi-Dunitz angle of 90-110° (Figure 3A). 5,16,28 Comparison of the three cryo-EM models with aminobenzoic acid monomers in the A site revealed that, while the conserved base pair between C75 in A-site tRNA and G2553 in 23S rRNA is retained (Figure 2), the positioning of the aromatic ring in the A-site cleft formed by A2451 and C2452 shifts the position of the monomer within the PTC, especially the nucleophilic amine, relative to that of an l -α-amino acid (Supplementary Figure S12). In the case of the m ABZ monomer, the aromatic ring could be modeled in two distinct conformations that differ by a 180° rotation about the aryl-carbonyl bond (Figure 1C).…”
Section: Resultsmentioning
confidence: 99%
“…Notably, in all three experimental structures (Apy, o ABZ, and m ABZ), the P-site carbonyl oxygen is rotated towards the A-site monomer and lies almost in the same plane as the A-site nucleophile (Figure 3). 5,16,28 . Although these distances and orientations differ from those seen for properly positioned α-amino acids, 5,16,23 the observation of in vitro reactivity suggests that, at least for Apy and o ABZ, the exocyclic amino group is positioned just close enough to allow amide bond formation under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Since H1, H94, and H98 play a role in the stability of the E. coli LSU, we wondered whether these helices play similar roles in other bacterial ribosomes. We examined the region surrounding H1 in various high resolution structures of bacterial ribosomes that contain H98 (Table 1) (32)(33)(34)(35)(36)(37)(38)(39)(40)(41). Out of the surveyed structures, the ribosomes from two organisms, P. aeruginosa and E. faecalis, have interactions between H1, H94, and H98 that form the same structure as in the E. coli ribosome.…”
Section: Discussionmentioning
confidence: 99%
“…Wild-type deacylated initiator tRNAi fMet was overexpressed and purified from E. coli as described previously (22)(23)(24)(25). The complex of the wild-type T. thermophilus 70S ribosome with mRNA, vacant A site, and P-site tRNAi fMet was formed as described previously (20,21,23) in the presence of 500 µM THR.…”
Section: X-ray Crystallographic Structure Determinationmentioning
confidence: 99%
“…Collection and processing of the X-ray diffraction data, model building, and structure refinement were performed as described in our previous reports (20,21,23,24,26,27). Diffraction data were collected at beamlines 24ID-C and 24ID-E at the Advanced Photon Source (Argonne National Laboratory).…”
Section: X-ray Crystallographic Structure Determinationmentioning
confidence: 99%